Malaysian foreign policy in the Mahathir era 1981-2003 dilemmas of development - Dhillon, Karminder Singh 1960- (NUS Press, 2009)
Malaysia's former Prime Minister Mahathir Mohamad is often seen as the sole author of the country's foreign policy. Malaysian Foreign Policy in the Mahathir Era shows that while Mahathir's personality, leadership style, political ideology and brand of nationalism unquestionably had a deep impact, so too did domestic issues and external forces associated with globalization. The book examines seven major foreign policy initiatives of the Mahathir period: buy British last, anti-commonwealth, look East, Third World spokesmanship, regional engagement, Islamic posturing and commercial and developmental diplomacy. In discussing these topics, the author explains the significance for foreign policy of communal concerns, the regime's need to maintain its own authority in the face of political and social initiatives (some rooted in Islam), and its desire to achieve national development. He also discusses external pressures, including Japan's regional designs, Singapore's defense posture and the growing importance of China for the region. The approach breaks away from the elitist decision making styles and single factor models usually employed to explain the foreign policy of developing nations, and establishes a direct link between domestic politics and foreign policy during the period studied, suggesting that the latter was truly an extension of the former.